Morphological Characteristics of Digestive Tract and Clark Index of Ellochelon vaigiensis (Quoy & Gaimard, 1825) in some Coastal Estuarine Areas in the Mekong Delta - Anh, Nguyen Thi Mai; Ton, Nguyen Huu Duc; Quang, Dinh Minh (VNU Journal of Science: Natural Sciences and Technology, 2022)
Ellochelon vaigiensis (Quoy & Gaimard, 1825) distributes widely from marine to brackish and freshwater in the Indo-Pacific region, including Vietnam. In the Mekong Delta, this fish distributes mainly in the estuaries and is a commercial value fish species. However, information about this fish digestive tract morphology and energy storage capacity had been still unknown. These characteristics, after being elucidated, wil be the basis for further research on artificially rearing them, contributing to the diversity of cultured subjects. This study was carried out in several coastal areas of provinces in the Mekong Delta from Ben Tre to Tra Vinh, Soc Trang and Bac Lieu. The analysis results of a total of 656 samples (289 females and 367 males) collected monthly, from March to October 2021, showed that E. vaigiensis had a small mouth, thick gill comb, short stomach and long intestines. This showed that they belong to the group of herbivorous fish. Ellochelon vaigiensis displayed a high energy storage capacity due to its relatively large Clark coefficient (0.73±0.03 SE). This value in the wet season (0.66±0.01 SE) is lower than in the dry season (0.85±0.01 SE, t=16.98, p<0.01). This value changed significantly according to the study sites (1-way ANOVA, F=4.50, p<0.01), with the highest value in Thanh Phu, Ben Tre (0.77±0.02 SE) and the lowest in Duyen Hai, Tra Vinh (0.70±0.02 SE), but this coefficient was not statistically significant between males (0.73±0.01 SE) and female (0.73±0.01 SE, t=0.64 p=0.52).